PERCEPTION OF AQUACULTURE EXTENSION PERSONNEL ON INFORMATION TECHNOLOGY ENABLED EXPERT SYSTEM FOR SHRIMP AQUACULTURE - ALAGAPPAN, M.; KUMARAN, M. (Journal of the Inland Fisheries Society of India, 2021)
Shrimp aquaculture is a knowledge intensive and high value farming enterprise in the coastal agro-ecosystems. An Expert System for Shrimp Aquaculture (ESSHA) was developed mainly for the knowledge management of field extension personnel using Visual Basic 6.0 and MS Access on Better Management Practices of shrimp farming. Its perceptions on the attributes of the expert system were studied among the end users i.e., aquaculture extension personnel. ESSHA was perceived as highly informative, less complex and compatible. It was validated for its technicality, feasibility and user friendly design. ESSHA as a knowledge management tool could be employed by research and development agencies for capacity building of the extension personnel and other end users including aqua farmers.Key words: Expert system, aquaculture, extension, knowledge dissemination, extension personnel